2010
DOI: 10.1175/2010jhm1249.1
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Snow Scheme for the ECMWF Land Surface Model: Description and Offline Validation

Abstract: A new snow scheme for the European Centre for Medium-Range Weather Forecasts (ECMWF) land surface model has been tested and validated. The scheme includes a new parameterization of snow density, incorporating a liquid water reservoir, and revised formulations for the subgrid snow cover fraction and snow albedo. Offline validation (covering a wide range of spatial and temporal scales) includes simulations for several observation sites from the Snow Models Intercomparison Project-2 (SnowMIP2) and global simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
259
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(281 citation statements)
references
References 56 publications
3
259
0
1
Order By: Relevance
“…in which S ↓ and L ↓ are the downwelling shortwave and longwave irradiances, and the last term is the upwelling longwave radiation for the assumed isothermal snowpack at T 0 = 273.15 K. The snow albedo (α S ) is parametrized prognostically through the continuous reset formulation following Dutra et al (2010), which computes the albedo for time increments t by distinguishing between accumulating, steady and ablating conditions:…”
Section: Mass and Energy Balancementioning
confidence: 99%
“…in which S ↓ and L ↓ are the downwelling shortwave and longwave irradiances, and the last term is the upwelling longwave radiation for the assumed isothermal snowpack at T 0 = 273.15 K. The snow albedo (α S ) is parametrized prognostically through the continuous reset formulation following Dutra et al (2010), which computes the albedo for time increments t by distinguishing between accumulating, steady and ablating conditions:…”
Section: Mass and Energy Balancementioning
confidence: 99%
“…At the surface, the snowpack is treated taking into account its thermal insulation properties and a representation of density (Dutra et al, 2010). The vertical resolution in the atmosphere near the surface is not as fine as in the MAR model.…”
Section: Meteorological Models and Microphysics Highlightsmentioning
confidence: 99%
“…Liston (2004) also developed a subgrid snow distribution to describe these two different processes and validated this method at the mesoscale (2500 km 2 ). More recently, Niu and Yang (2007) and Dutra et al (2010) introduced a hysteresis in the SCD by inversely relating the snow-cover area to the snowpack bulk density: as the snow density increases with respect to the snow age, the snow-cover area for a given quantity of snow gets lower later in the snow season. Although this study showed good consistency with satellite images of snow cover at a global scale (10 000 km 2 ), we concur with Swenson and Lawrence (2012) that the observed hysteresis is more likely due to the variability of topography or vegetation within the catchment than to the age of snow.…”
Section: Introductionmentioning
confidence: 99%